Investigation of Crinum solapurense leaves extract for antidiabetic activity and histopathological evaluation in an in-vivo experimental model - Sunayana Mali; Gaurav Jain; Jyotiram Sawale; Audumbar Mali (Phytomedicine Plus)
Background: This study investigates the biological activity of the newly discovered novel C. solapurense (Crinum solapurense) plant from the Solapur, Maharashtra region, addressing a literature gap on its properties. In this investigation, we have performed the plant's phytochemical, powder characteristics, and in-vivo antidiabetic activity. Evaluating ethanolic extract of C. solapurense leaves for in-vivo study gives valuable insights into its bioactive potential and histopathological investigation in dexamethasone-induced diabetic rats. Purpose: To evaluate the pharmacological activity and histopathological investigation of C. solapurense leaf extracts in an in-vivo experimental model in male albino Wistar rats. Methods: Ethanolic leaf extracts underwent successive extraction and phytochemical profiling. In-vivo antidiabetic activity and histopathological investigation were assessed in dexamethasone-induced diabetic rats. Results: After inducing diabetes in rats by using dexamethasone, various groups of rats were treated with distilled water, a standard antidiabetic drug used as a Glibenclamide (GLC), and lower, medium, and higher doses of C. solapurense leaf extracts like 100.00 mg/kg, 200.00 mg/kg & 400.00 mg/kg respectively. The C. solapurense leaf extracts significantly reduced blood glucose levels (BGL) in dexamethasone-induced male albino Wistar rats. At the same time, the best results were obtained at higher doses of C. solapurense leaf extracts (400 mg/kg body weight). The water intake & food intake in dexamethasone-induced male albino Wistar rats were significantly decreased however weight loss of rats was minimized at lower, medium, and higher doses of C. solapurense leaves extract. In the histopathological study, the higher dose of C. solapurense (400.00 mg/kg) showed very significant effects for the regeneration of cells for beta islets of Langerhans on hematoxylin and eosin-stained pancreas cells in dexamethasone-induced diabetic rats. Conclusion: The ethanolic leaf extract of newly discovered C. solapurense possesses in-vivo antidiabetic properties in dexamethasone-induced male albino Wistar rats, preventing different complications of diabetes mellitus. It could be useful for the treatment of diabetes mellitus (DM).